Galactic chemical evolution and GRB host identification. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Matteucci, Francesca; Grieco, Valentina
Abstract: We describe a method to identify GRB host galaxies by means of their chemical abundances. We apply this method to three GRB hosts by comparing detailed chemical evolution models, including dust, of galaxies of different morphological type to observed abundance ratios. We conclude that none of them is likely to be a dwarf irregular galaxy, as it is believed for the majority of GRB hosts, but rather two of them (GRB081008 and GRB120327A) are likely to be spirals and the third is likely to be an elliptical (GRB120815). In addition, we have derived their chemical ages: in particular, the elliptical host is only 15 Myr old, while the other two hosts are 50 Myr (GRB120327A) and 320 Myr (GRB130815).